Catheter-Free Arrhythmia Ablation Using Scanned Proton Beams: Electrophysiologic Outcomes, Biophysics, and Characterization of Lesion Formation in a Porcine Model. (October 2020) - Suzuki, Atsushi; Deisher, Amanda J.; Rettmann, Maryam E.; Lehmann, H. Immo; Hohmann, Stephan; Wang, Songyun; Konishi, Hiroki; Kruse, Jon J.; Cusma, Jack T.; Newman, Laura K.; Parker, Kay D.; Monahan, Kristi H.; et al.
Abstract : Background: Proton beam therapy offers radiophysical properties that are appealing for noninvasive arrhythmia elimination. This study was conducted to use scanned proton beams for ablation of cardiac tissue, investigate electrophysiological outcomes, and characterize the process of lesion formation in a porcine model using particle therapy. Methods: Twenty-five animals received scanned proton beam irradiation. ECG-gated computed tomography scans were acquired at end-expiration breath hold. Structures (atrioventricular junction or left ventricular myocardium) and organs at risk were contoured. Doses of 30, 40, and 55 Gy were delivered during expiration to the atrioventricular junction (n=5) and left ventricular myocardium (n=20) of intact animals. Results: In this study, procedural success was tracked by pacemaker interrogation in the atrioventricular junction group, time-course magnetic resonance imaging in the left ventricular group, and correlation of lesion outcomes displayed in gross and microscopic pathology. Protein extraction (active caspase-3) was performed to investigate tissue apoptosis. Doses of 40 and 55 Gy caused slowing and interruption of cardiac impulse propagation at the atrioventricular junction. In 40 left ventricular irradiated targets, all lesions were identified on magnetic resonance after 12 weeks, being consistent with outcomes from gross pathology. In the majority of cases, lesion size plateaued between 12 and 16 weeks. Active caspase-3 was seen in lesions 12 and 16 weeks after irradiation but not after 20 weeks. Conclusions: Scanned proton beams can be used as a tool for catheter-free ablation, and time-course of tissue apoptosis was consistent with lesion maturation. Abstract : Supplemental Digital Content is available in the text.